2017
DOI: 10.1177/2158244017725129
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Personality Traits (DSM-5), Risk Factors, and Mental Health

Abstract: In Section III of the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5; American Psychiatric Association [APA], 2013), a dimensional model of maladaptive personality traits is proposed. This model coexists with, and is an alternative to, the traditional categorical taxonomy and defines a personality trait as a tendency to feel, perceive, behave, and think in relatively consistent ways across time and across situations. Although consistent, traits may also change throughout one's life (APA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 40 publications
(73 reference statements)
4
29
0
7
Order By: Relevance
“…This instrument is the short version of the 220-item inventory and it assesses the main five domains with 25 items: Antagonism (e.g., “It is not so bad to hurt someone’s feelings,”) Detachment (e.g., “I stay away from romantic relationships,”) Disinhibition (e.g., “I feel as if I acted completely on impulse,”) Negative Affect (e.g., “I worry about almost everything,”) and Psychoticism (e.g., “I have seen things that weren’t really there”). Regarding its psychometric properties, the Argentinean local study provided evidence for the five-factor structure, and of divergent validity and good internal consistency ( Góngora and Castro Solano, 2017 ). In this sample, Cronbach’s alphas for all traits indicated good internal consistency (>0.70).…”
Section: Methodsmentioning
confidence: 99%
“…This instrument is the short version of the 220-item inventory and it assesses the main five domains with 25 items: Antagonism (e.g., “It is not so bad to hurt someone’s feelings,”) Detachment (e.g., “I stay away from romantic relationships,”) Disinhibition (e.g., “I feel as if I acted completely on impulse,”) Negative Affect (e.g., “I worry about almost everything,”) and Psychoticism (e.g., “I have seen things that weren’t really there”). Regarding its psychometric properties, the Argentinean local study provided evidence for the five-factor structure, and of divergent validity and good internal consistency ( Góngora and Castro Solano, 2017 ). In this sample, Cronbach’s alphas for all traits indicated good internal consistency (>0.70).…”
Section: Methodsmentioning
confidence: 99%
“…Starting from these considerations, we expected that participants with clinically relevant emotional problems may be efficiently discriminated by negative affectivity and detachment domains, as well as by non-scientifically supported causal beliefs. Indeed, previous findings showed that Negative Affectivity and Detachment were negatively associated with emotional well-being (e.g., Góngora & Castro Solano, 2017). Recently, Lai et al' (2020) showed in a sample of 1257 health care workers that women experienced more psychological burden than male participants.…”
Section: Introductionmentioning
confidence: 94%
“…Instruments related to the AMPD have been translated into a number of different languages and cultural contexts. For example, the PID-5 is available and has been successfully applied in Arabic [71], Brazilian [72,73] 63,86], and Swedish [64]. Further developments are underway on assessing severity and style according to the AMPD.…”
Section: Further Issuesmentioning
confidence: 99%